In Vitro, in Vivo, and Interaction Studies of Nematophagous Fungus Arthrobotrys thaumasia (Monacrosporium thaumasium) with the Larvae of Trichostrongylides of Sheep - Dai, Hong-Wei; Xu, Qiang; Wang, Bo-Bo; Jia, Xiao-Ye; Wan, Xue-Mei; Yang, Xue-Cai; Cai, Kui-Zheng; Liu, Zhen-Bin (The Journal of parasitology, 2017)
It is important to isolate potential candidates from the local isolates of nematophagous fungi and to investigate interaction between the fungal strains and gastrointestinal nematodes for the biological control of parasitic nematodes in livestock. In the present study, we assessed the in vitro predatory activity and the viability of isolates of Arthrobotrys thaumasia (Monacrosporium thaumasium) after passage through the gastrointestinal tract of sheep. The predatory process of a representative isolate selected against the larvae of trichostrongylids was prepared with a scanning electron microscope (SEM). In vitro experiments tested the ability of 9 native isolates of A. thaumasia to prey on larvae of feces of sheep infected with natural mixed nematodes (Haemonchus contortus, Trichostongylus colubriformis, Marshallagia mongolica). These isolates of A. thaumasia decreased infectivity of third stage infective larvae (L3) by 75.54–99.97%; 7 isolates decreased infectivity by more than 90%. In vivo experiments also demonstrated significant reductions of L3 numbers in the feces treated with the 9 isolates after passing through the gastrointestinal tract of sheep, and these decreases ranged from 51.68 to 88.16%. The isolates tested were re-isolated in 5-g sub-samples of feces from sheep in each treatment group, indicating that these isolates had the capacity to prey upon larvae of trichostrongylids after the passage through gastrointestinal tract. SEM shows that at 6 hr after the larvae were added, including the second stage larvae (L2) and L3 of trichostrongylids, the isolate NBS 005 caught them; at 8 hr after being caught L2 was penetrated by the fungus while penetration of L3 occurred at 12 hr; at 78 hr post-capture L2 was completely destroyed by the fungus while complete digestion of L3 occurred at 84 hr.